(untitled) (`, 2024)
This research paper explains the role of women in Saraiki poet Ashu Lal’s poetry. This paper Undercurrent modern Saraiki poetry through the lens of Simone de Beauvoir. This study finds the feminist dimensions in Ashu Lal’s poetry. He sketches similarities with Simone de Beauvoir’s existentialist philosophy. He uses Hindi mythology to depict the agony, pain, and difficulties of females and relates them to "Birha Warti Nari." Saraiki poetry is rich in cultural distinctions. He uses echo feminism and portrays the woman with a dolphin as "Bhulhun." He offers a unique perspective on women’s experiences and struggles through a qualitative analysis. The folk lores female characters Saasi, Heer identifies themes of identity, agency, and obstruction resounding Beauvoir’s notion that "one is not born, but rather becomes, a woman." This study emphasized how Seraiki poets navigate patriarchal societal norms, declaring women’s freedoms and challenging traditional gender roles. Keywords: poetry, female, gender, feminism, identity